2007
DOI: 10.1007/s12026-007-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Acquired immunologic tolerance: with particular reference to transplantation

Abstract: The first unequivocally successful bone marrow cell transplantation in humans was recorded in 1968 by the University of Minnesota team of Robert A. Good (Gatti et al. Lancet 2: 1366-1369, 1968). This achievement was a direct extension of mouse models of acquired immunologic tolerance that were established 15 years earlier. In contrast, organ (i.e. kidney) transplantation was accomplished precociously in humans (in 1959) before demonstrating its feasibility in any experimental model and in the absence of a defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 99 publications
(149 reference statements)
2
12
0
1
Order By: Relevance
“…These findings support the concept that gradual reduction of immunosuppression is a key component of strategies to induce spontaneous tolerance in liver transplantation [24]. 'Tolerogenic' protocols Reports in adult LTx recipient have shown that operational tolerance can be achieved if there is a balance between donor cells and antidonor T cells [25 ].…”
Section: Calcineurin Inhibitor Minimizationsupporting
confidence: 78%
“…These findings support the concept that gradual reduction of immunosuppression is a key component of strategies to induce spontaneous tolerance in liver transplantation [24]. 'Tolerogenic' protocols Reports in adult LTx recipient have shown that operational tolerance can be achieved if there is a balance between donor cells and antidonor T cells [25 ].…”
Section: Calcineurin Inhibitor Minimizationsupporting
confidence: 78%
“…After 3 weeks of low dose daily tacrolimus, right lobar LDLT was performed with continued minimum daily tacrolimus. The strategy in these 10 patients is described elsewhere [16]. …”
Section: Resultsmentioning
confidence: 99%
“…After complete removal of the recipient's diseased liver, the donor right lobe was transplanted to the vacated hepatic fossa, with technical variations that were dictated largely by anatomic variations in both the recipient and donor [14,15]. In addition to the hepatic allograft, 10 recipients during the last third of the experience (October 2005–October 2006) also were given an infusion of unmodified mononuclear cells obtained from the donor by leukopheresis [16]. …”
Section: Methodsmentioning
confidence: 99%
“…3,4 This phenomenon may be a prerequisite for the maintenance of induced clonal deletion, a critical mechanism for acquired tolerance following transplantation. [5][6][7] Since the pioneering study by Starzl et al evaluating persistent systemic microchimerism in long-term allograft recipients, many clinical trials have been performed to confirm whether DBMC infusion can promote donor specific hyporesponsiveness thus improving long-term allograft survival. 4 However, only a limited number of trails (8)(9)(10)(11)(12) showed specific hyporesponsiveness and improved allograft survival in DBMC infused recipients compared with non-infused transplant recipients.…”
Section: Introductionmentioning
confidence: 99%